KONTAMINASI SEL DARAH MERAH PADA SISA LARUTAN ANESTESI DALAM CARTRIDGE PASCA INJEKSI ANESTESI LOKAL MENGGUNAKAN SYRINGE INTRALIGAMEN X - Moh. Danil Ahsan Murdiputra; Budiono -; Hayyu Failasufa (Universitas Muhammadiyah Semarang, 2017)
Background: Local anesthetic is often used in the dental practice as a pain management to the patient before the surgery procedure. Theories about blood pressure and fluid shows that blood pressure in the vessels can deliver a reverse pressure on the anesthetic solution and it allows blood contamination.Blood as a disease carriers, can deliver blood-borne diseases like HIV, Hepatitis B, malaria, and other infectious disease. The aim of this research is to study red blood cells contamination on the residual anesthetic solution inside the cartridge after local anesthetic injection using X intra-ligament syringe. Methods: Cartridge containing lidocaine hydrochloride 2% and epinephrine 1:80.000 is the material used in this research. Ten cartridges were given to the dentists. The residual anesthetic solution that have been used will be observed in the laboratory. The residual anesthetic solution were observed using Urinalysis Reagent Strips (Urine). This observational analytic research use a cross sectional design and the sampling methods was accidental sampling. Point-biserial correlation were used for data analyze. Results: 33 samples had been obtained from the dentists. The results was 23 samples (69,7%) revealed red blood cells contamination and ten samples (30,3%) didn't reveal red blood cells contamination. There was a close relationship between red blood cells contamination on the residual anesthetic solution (r = - 0,572) and a significant relationship between red blood cells contamination on the residual anesthetic solution with P-value 0,001 (P < 0,01; H0 was rejected). Conclusion: This research conclude that there was red blood cells contamination on the residual anesthetic solution in the cartridge using X intra-ligament syringe. Keywords: red blood cells contamination, residual anesthetic solution, intra-ligament syringe.